Sosialisasi Pentingnya Menjaga Kebersihan di Ruang Publik untuk Kenyamanan dalam Beraktivitas - Karim, Abbas; Rahmanto, Achmad; Chaidir, Kholid (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
The aim of this activity is to socialize the importance of cleanliness in public spaces for comfort in daily activities. The methods used are: 1) documenting the location of activities before cleaning; 2) remove grass that grows inside and outside the gutter; 3) cutting down grass growing on the sides of public roads; and 4) sweeping and lifting rubbish inside and outside the gutter, as well as rubbish on the side of the road and then disposing of it in its place. The results of the activities that have been achieved are through socializing the importance of maintaining cleanliness in public spaces by partnering with the University of Riau and the local community of Rawang Empat, Bandar Petalangan District, Pelalawan Regency, which can increase insight into environmental cleanliness. People in the Rawang Empat environment have become more aware of implementing clean and healthy living habits, and can differentiate between organic and non-organic waste. Other positive impacts of this activity include: 1) avoiding the threat of flooding; 2) avoid infectious diseases; 3) improve physical and spiritual health; 4) maintain harmony between neighbors; and 5) cleanliness can create a comfortable, peaceful, beautiful and enjoyable environment.